2023
DOI: 10.3390/cells12131717
|View full text |Cite
|
Sign up to set email alerts
|

3′UTR of mRNA Encoding CPEB Protein Orb2 Plays an Essential Role in Intracellular Transport in Neurons

Abstract: Intracellular trafficking plays a critical role in the functioning of highly polarized cells, such as neurons. Transport of mRNAs, proteins, and other molecules to synaptic terminals maintains contact between neurons and ensures the transmission of nerve impulses. Cytoplasmic polyadenylation element binding (CPEB) proteins play an essential role in long-term memory (LTM) formation by regulating local translation in synapses. Here, we show that the 3′UTR of the Drosophila CPEB gene orb2 is required for targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For example, the already mentioned protein known as GAP-43 is a presynaptic phosphoprotein that probably functions as a coordinating center for a large group of proteins and kinases involved in axonal structure and function, as well as in synapse plasticity control [ 126 , 127 ]. As long as it concerns the CPEB protein, its importance at the level of synapses has also been confirmed by recent experiments in Drosophila that demonstrated that, when the 3′UTR of its mRNA is deleted, the protein (known as Orb2 in this organism) is no longer specifically localized and, as a result, a clear deficit is found in the process of long-term memory acquisition [ 128 , 129 ]. Recently, it has been suggested that the critical role of CPEB proteins in translational control can depend on protein–protein interaction, based on the low-complexity motifs (LCMs), that indeed keep together different proteins in the already mentioned RNA-containing granules [ 130 ].…”
Section: Post-transcriptional Regulation and Synaptic Plasticity In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the already mentioned protein known as GAP-43 is a presynaptic phosphoprotein that probably functions as a coordinating center for a large group of proteins and kinases involved in axonal structure and function, as well as in synapse plasticity control [ 126 , 127 ]. As long as it concerns the CPEB protein, its importance at the level of synapses has also been confirmed by recent experiments in Drosophila that demonstrated that, when the 3′UTR of its mRNA is deleted, the protein (known as Orb2 in this organism) is no longer specifically localized and, as a result, a clear deficit is found in the process of long-term memory acquisition [ 128 , 129 ]. Recently, it has been suggested that the critical role of CPEB proteins in translational control can depend on protein–protein interaction, based on the low-complexity motifs (LCMs), that indeed keep together different proteins in the already mentioned RNA-containing granules [ 130 ].…”
Section: Post-transcriptional Regulation and Synaptic Plasticity In T...mentioning
confidence: 99%
“…Also, in this case, it seems that the sequence of polyglutamine is essential for memory formation [ 197 ]. However, it is now known that the Drosophila counterpart, Orb2, and the ApCPEB isoform can be found in the soluble form or in the β-sheet-rich amyloid form, which has greater binding capacity for mRNAs and, although they have low sequence homology, both of them have N-terminal domains that drive aggregation, following synapse activation [ 128 , 129 , 200 ].…”
Section: Post-transcriptional Regulation and Synaptic Plasticity In T...mentioning
confidence: 99%